Treatment outcomes of concurrent hyperthermia and chemoradiotherapy for pancreatic cancer: Insights into the significance of hyperthermia treatment - Maebayashi, Toshiya (Oncol Lett, 2017)
Patients with locally advanced unresectable pancreatic cancer (LAUPC) have a poor prognosis. In addition their quality of life impaired by cancer pain and biliary tract infections. Therefore, multimodality therapy and selection of optimal treatment methods are essential for achieving prolonged survival. The present study investigated the significance of using hyperthermia concurrently with multimodality therapy to improve treatment outcomes in patients with LAUPC. In total, 13 patients receiving concurrent hyperthermia and chemoradiotherapy (HCR) or chemoradiotherapy (CR) alone for LAUPC between 2002 and 2013 were analyzed retrospectively. Of the 13 patients, 5 received concurrent HCR and 8 received CR. The chemotherapy regimens were 5-fluorouracil (5-FU) in 5 patients and gemcitabine hydrochloride (GEM) in the other 8. Patients who gave consent for hyperthermia treatment received GEM plus CR. The median overall survival period for all patients was 12 months and the 1-year survival rate was 55%; the corresponding values were 12 months and 57% in the GEM CR group, and 15 months and 80% in the HCR group. Univariate analyses was perfomed to identify factors predicting recurrence after treatment. The potential prognostic factors analyzed were: Age, sex, performance status, location, tumor size, the tumor marker CA 19-9, total radiation dose, chemotherapy and hyperthermia. Univariate analysis for factors associated with outcomes revealed a significant difference favoring the HCR group [relative risk=15.97 (95% confidence interval: 12.87–19.83) P=0.021]. In conclusion, hyperthermia merits active recommendation to pancreatic cancer patients who have a positive attitude toward this treatment and whose performance status is satisfactory.